Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1740-0929.2009.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of inclusion levels of urea‐treated potato pulp silage in concentrate and roughage sources on finishing performance and carcass quality in cull beef cows

Abstract: An experiment was conducted to determine the effects of inclusion levels of potato pulp silage in concentrate (0, 15, 30 or 45%; on a dry matter basis) and roughage sources (rice straw or wheat straw) on finishing performance and carcass quality of cull beef cows. Sixteen Japanese Black (Wagyu) mature cull cows (490 +/- 31 kg of BW) were used in this experiment. Increasing the levels of potato pulp silage in concentrate and roughage sources did not significantly affect feed intake in cows. In addition, the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Furthermore, there is a positive correlation between the marbling score and L* values of meat (Wulf et al . 1997; Sugimoto et al . 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is a positive correlation between the marbling score and L* values of meat (Wulf et al . 1997; Sugimoto et al . 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Boles et al (2004) indicated that the increase in lightness could be associated with antemortem muscle glycogen content and its relationship with the ultimate pH or rate of pH decline post mortem. Furthermore, there is a positive correlation between the marbling score and L* values of meat (Wulf et al 1997;Sugimoto et al 2009). This relationship between L* and intramuscular fat content could be explained by the fact that fat is generally white and L* is a value on an axis from black to white (Wulf & Wise 1999).…”
Section: Colormentioning
confidence: 95%
“…) and diet (Sugimoto et al . ). The meat color shows redder tonalities in older cattle because the myoglobin content of the muscles increases with age.…”
Section: Discussionmentioning
confidence: 97%
“…The best economical efficiency was recorded with ration D (1.69) followed rations B, C and A. Sugimoto et al (2009) and Aibibula et al (2007) mentioned that potato pulp silage can be low-cost feed source for livestock feeding. Generally, the price of potato, sweet potato and turnip and consequently its silages is directly affect feed cost and economical efficiency of the rations when compared with price of traditional feed ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…Nkosi and Ratsaka (2010) found that feed conversion was 10.2 of lambs fed ration containing 22.5% silage of potato hash and hay + CFM. Potato pulp can be low cost feed sources for livestock (Sugimoto et al, 2009). This work aimed to study the effect of rations containing silages of non-commercial potato tubers, sweet potato roots, and turnip roots with rice straw on lamb's performance and its economical efficiency.…”
Section: Introductionmentioning
confidence: 99%